Evaluation of the impacts of micro-business operations on the quality of urban environment: A case study of Iwo, Southwestern Nigeria - Ogunbode, Timothy O.; Oyelude, Opeyemi; Oyebamiji, Victor O. (Frontiers in Sustainable Cities, 2022)
A sustainable environmental quality is a prerequisite to a sustainable human livelihood. This work evaluated the impacts of micro-business enterprises (MBEs) on the quality of urban environment with Iwo, Nigeria, as a case study. A survey across the identified micro businesses across the city brought about four categorizations which was based on the kinds of wastes being generated. Fifty-nine business units were randomly selected from each category, thus, making a total of 236 in all, for the survey in order to generate the required data. The data was subjected to both descriptive and inferential statistics. The results showed that 75.01 of the respondents have spent between 11 and 15 years in their respective enterprises while the volume of wastes being generated by 76.69% of the MBEs fell in the ‘moderately high’ category and 71.19% did not associate any illness to the waste generated by the MBEs. The results of Factor Analysis showed that nine factors explained 82.914% of how MBEs have impacted on the quality of the urban environment. The results further showed that bad odours from the waste generated by the MBEs topped the variables with the highest predictive power (19.032%) while the waste characteristics offer the least explanation (3.279%). However, the 60.96 percent bulk of the 100% explanation was made by the top three variables namely bad odours from the waste generated by the MBEs, Government’s monitoring role and the hindrances posed by the wastes. The work, therefore, concludes that the MBEs could be more beneficial to human livelihood and the physical environment rather than being detrimental, if both the entrepreneurs (the citizens) and the government adhere to their respective responsibilities. Relevant authorities in Nigeria should initiate policies that are capable of stimulating the growth of entrepreneurial activities with effective regulation to curtail urban degradation for improved livelihood. It is suggested that further studies on the compliance of MBE operators to the established governing rules be carried out.